The Urban Coastal Settlement Management Strategy of Bumi Waras Sub-District, Bandar Lampung - Putri, Septi Malidda Eka; Wahono, Endro P.; Reza, Muhammad; Azkia, Lana Izzul (Coastal and Ocean Journal (COJ), 2024)
Indonesia's extensive coastal areas face significant environmental and social challenges, particularly in densely populated regions like Bumi Waras Sub-district, emphasizing the urgent need for integrated coastal management to ensure sustainable development and improve community living conditions. This study aims to ascertain the future course of urban coastal settlement management measures. The study was conducted in Bandar Lampung's Bumi Waras Sub-District's coastal region, as the second-highest population sub-district in Bandar Lampung City. The samplings were chosen purposively by expert assessments and the community. Direct interviews were used to collect data, while the SWOT method was used to analyze the result. The results of the Internal Factors Analysis Summary matrix score of 3.167 and the External Factors Analysis Summary matrix at 3.153, indicating fairly good growth conditions. The highest priority strategy, 4.028, was the "weaknesses and threats" (WT) parameter, highlighting the need to address limited community participation in planning, implementing, and supervising coastal area management, as well as the lack of private sector involvement. Therefore, the recommended strategy is to enhance human resource capacity through socialization and counseling on urban coastal settlement management. Additionally, efforts should be directed toward optimizing the utilization of existing facilities and infrastructure to reduce environmental damage and promote sustainable coastal area management.